2018
DOI: 10.3389/fvets.2018.00050
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Behavioral Characteristics of Dogs Purpose-Bred and Prepared to Perform Vapor Wake® Detection of Person-Borne Explosives

Abstract: Specialized detector dogs are increasingly being utilized for the detection of modern threats. The Vapor Wake® (VW) dog was developed to create a dog phenotype ideally suited for detecting hand-carried and body-worn explosives. VW dogs (VWDs) are trained to sample and alert to target odors in the aerodynamic wakes of moving persons, which entrains vapor and small particles from the person. The behavioral characteristics necessary for dogs to be successfully trained and employed for the application of VW are a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 34 publications
(72 reference statements)
1
36
0
1
Order By: Relevance
“…Behavioral traits—Behavioral traits also play critical roles in the determination of the success or failure of future HRDDs’ training [ 19 , 61 , 63 ]. The behavioral response of a dog facing a particular stimulus is driven by two main components: its temperament and its personality [ 21 , 64 , 65 , 66 ].…”
Section: Selection Of Human Remains Detection Dogsmentioning
confidence: 99%
See 1 more Smart Citation
“…Behavioral traits—Behavioral traits also play critical roles in the determination of the success or failure of future HRDDs’ training [ 19 , 61 , 63 ]. The behavioral response of a dog facing a particular stimulus is driven by two main components: its temperament and its personality [ 21 , 64 , 65 , 66 ].…”
Section: Selection Of Human Remains Detection Dogsmentioning
confidence: 99%
“…Temperament can be defined as the individual difference in behavioral responses, which is steady among time and context, that are grounded in affective state and its regulatory processes and which are evident from an early age [ 67 ]. It usually has genetic predisposition [ 58 , 63 , 67 , 68 ]. Personality is the result of both a dog’s genetics and experiences over time, which shapes the dog’s behavioral response to situational events [ 19 ].…”
Section: Selection Of Human Remains Detection Dogsmentioning
confidence: 99%
“…Similarly, an analysis of the tests used to measure suitability of MWDs for the Swedish Armed Forces revealed that physical and social engagement were interrelated and both were predictive of training outcomes (27). Possession of an object and corresponding engagement with a handler during a tug game has also been shown to be predictive of suitability as an EDD as early as 6 months of age, indicating that this trait may be relatively genetically influenced and stable across development (16).…”
Section: Reward Valuementioning
confidence: 96%
“…Potential advantages of using natural air-scenting breeds for detection work have not been systematically explored, and current evaluation methods do not typically account for these natural preferences (9). However, in a recent examination of the behavioral characteristics associated with dogs bred and trained for PBIED tasks, air-scenting ability assessed at 6 months was predictive of dogs' future placement as a PBIED EDD vs. traditional EDD, and was the only behavioral measure that distinguished the two types of outcomes at this age (16). This finding is consistent with the notion that air-scenting has a genetic basis, with such predispositions appearing earlier in development before extensive training may obscure differences.…”
Section: Search Techniquementioning
confidence: 99%
“…The value of traditional behavioral assessments is not overlooked; rather, their use in conjunction with concurrent measures will enhance their utility. For example, we recently published an examination of the behavioral characteristics related to success in a particular population of specialized explosives detection dogs (Lazarowski et al, 2018). Although we were able to identify a number of traits associated with success, the subjective nature of the assessments used to evaluate behavioral characteristics limits early predictability and overall generalizability.…”
Section: Abstract: Canine Cognition Detection Dogs Canine Fmrimentioning
confidence: 99%